ON VARIETY OF INTEGRATION PROCESSES IN EUROPE - L. S. Voronkov (Vestnik MGIMO-Universiteta)
On the basis of analysis of integration processes between Nordic, Benelux countries and post-soviet states in Europe the author expresses hesitations in accepting the integration experiences gained by the EU as the criterion of efficiency and the pattern for the post-Soviet space. He does not consider that an involvement of all countries with market economy into processes of regional integration, if they do not try to achieve certain political aims through integration, is the universal regularity in the globalized world. In these cases neither free trade zones nor custom unions can be considered as integration stages, but they continue to be the tools for further development of trade. The author proposes to assess the EU evolution with regard to the legal norms of international organizations, where state sovereignty of members is strengthened, not given up to supernational bodies. In case the idea of reestablishment of an unified state on the remains of the former USSR, linked to the necessity to hand over the recently acquired sovereignty to it, is laid down to the ground for practical measures of integration, this kind of integration will hardly be attractive to the potential post-Soviet participants. This perspective is hardly desired for Russia either. The integration path of the EU reflects the peculiarities of the European situation and specific interests of its member states. Many details of the EU activity are not applicable to other integration groupings in Europe and membership criteria in every of them is not universal. Any efforts to construct integration processes in the post-Soviet space in accordance to the EU model without proper consideration to integration experiences of other countries and to political, economic, social, cultural, demographic, military peculiarities of the countries concerned seem to be not acceptable and founded.